Feasibility of Subxiphoid Anatomic Pulmonary Lobectomy in a Canine Model. (June 2016) - Hsieh, Ming-Ju; Yen-Chu,; Wu, Yi-Cheng; Yeh, Chi-Ju; Liu, Chieng-Ying; Liu, Chia-Chuan; Ko, Po-Jen; Liu, Yun-Hen
Purpose . Transthoracic thoracoscopic approach is the gold standard in surgical treatment for thoracic disease. However, it is associated with significant chronic postoperative wound discomfort. Currently, limited data are available regarding the subxiphoid approach to the thoracic cavity. The present study is aimed to evaluate the performance of a subxiphoid anatomic pulmonary lobectomy (SAPL) in a canine model. Methods . The SAPL procedure was performed in 10 beagle dogs using a 3-cm incision over the xiphoid process. After thoracic exploration, SAPL was performed under flexible bronchoscopy guidance. The pulmonary vessel was divided with Ligasure and secured with a suture ligature. The bronchus was divided with endostapler. Surgical outcomes were evaluated by the success of SAPL and operative complications. Results . SAPL was successfully completed in 9 animals. One animal required conventional thoracotomy to resuture the pulmonary artery stump. Another animal encountered small middle lobe laceration after SAPL and died at 8 days postoperation due to respiratory distress. Conclusion . Subxiphoid anatomic pulmonary lobectomy is technically feasible. Refinement of endoscopic instruments combined with more research evidences may facilitate the development of subxiphoid platform in thoracic surgery.